2013
DOI: 10.1038/cddis.2013.250
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine control of tissue regeneration and cell proliferation by Caspase-3

Abstract: Executioner caspases such as Caspase-3 and Caspase-7 have long been recognised as the key proteases involved in cell demolition during apoptosis. Caspase activation also modulates signal transduction inside cells, through activation or inactivation of kinases, phosphatases and other signalling molecules. Interestingly, a series of recent studies have demonstrated that caspase activation may also influence signal transduction and gene expression changes in neighbouring cells that themselves did not activate cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 67 publications
(76 reference statements)
1
65
0
Order By: Relevance
“…33 Caspase-3 is a potent, terminal caspase that executes apoptosis. 34,35 Despite advances in the pathogenesis of oxidative stress in ALI, the underlying molecular mechanism remains poorly clarified.…”
Section: Discussionmentioning
confidence: 99%
“…33 Caspase-3 is a potent, terminal caspase that executes apoptosis. 34,35 Despite advances in the pathogenesis of oxidative stress in ALI, the underlying molecular mechanism remains poorly clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating cell death, previous studies have demonstrated that caspase-3 also has fundamental roles in signal transduction (10,11 of the normal cellular metabolism of oxygen; however, a dramatic increase in ROS levels may lead to oxidative stress. It has been demonstrated that ROS induced by ionizing radiation are capable of triggering oxidative cellular damage and stimulating the activation of intracellular signaling pathways (12).…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-8 plays an important role in caspase activation cascades, activating downstream effector caspases such as caspase-3, -6, and -7 that lead to apoptosis [18] . On the other hand, oncotic cell death can be mediated by porimin, a highly glycosylated protein and member of the cell membraneassociated mucin family located on the cell surface [19] . For example, oncosis-like cell death can be mediated by introduction of porimin cDNA into Jurkat cells [20] .…”
Section: Introductionmentioning
confidence: 99%